Persuasive Elements in Fast-Food Advertisements: Teenagers’ Interpretations Through the Elaboration Likelihood Model Framework - La Sunra; Sahril Nur; Putri Cahyani (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study explores how persuasive elements in fast-food advertisements influence teenagers’ attitudes and perceptions. Using a qualitative descriptive approach, ten popular McDonald’s and KFC advertisements on YouTube released in the past five years were analyzed. Each ad featured celebrity collaborations, vibrant visuals, and strong audience engagement. Visual, verbal, and audio components were examined through a semiotic framework focusing on denotation, connotation, and underlying cultural meanings. The findings reveal that teenagers mostly respond to advertisements through emotional and visual cues rather than rational evaluation. Elements such as celebrity endorsements, catchy music, humor, bright color schemes, and limited time offers strongly shaped their attitudes toward fast-food brands. A smaller group of students considered product quality and value, but these instances were less common. Overall, the advertisements present fast-food consumption as part of a modern and desirable lifestyle, influencing how teenagers form preferences and social identities. The results highlight the need for stronger media literacy and educational programs that help young people critically assess persuasive messages in digital marketing and make more informed choices in their daily media consumption.